THE PRAGMATICS AND DISCOURSE ANALYSIS OF FANTASY CONCEPTS (Journal of Universal Science Research, 2025)
This paper explores the pragmatics and discourse analysis of fantasy concepts, focusing on how language constructs meaning and interaction in fantastical narratives. Key pragmatic elements such as speech acts, implicature, presupposition, and deixis are examined to illustrate their role in world-building and immersive storytelling.